2016
DOI: 10.1007/s11325-016-1353-9
|View full text |Cite
|
Sign up to set email alerts
|

ENT-specific therapy of obstructive sleep apnoea in adults

Abstract: The German Society of Otorhinolaryngology, Head and Neck Surgery recently has released the abbreviated version of its scientific guideline "ENT-specific therapy of obstructive sleep apnoea (OSA) in adults", which has been updated in 2015 and can be found online at the Association of the Scientific Medical Societies (Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften, AWMF). A summary of the main recommendations is provided in this revised English version. All recommendations are based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…6 Otolaryngology Department, Clinica Universitaria de Navarra, Pamplona, Spain. 7 Otolaryngology Department, Ospedale Morgagni-Pierantoni, Forli, Italy. 8 Department of Otolaryngology -Head and Neck Surgery, Rabin Medical Center, Petach Tikva, Israel.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Otolaryngology Department, Clinica Universitaria de Navarra, Pamplona, Spain. 7 Otolaryngology Department, Ospedale Morgagni-Pierantoni, Forli, Italy. 8 Department of Otolaryngology -Head and Neck Surgery, Rabin Medical Center, Petach Tikva, Israel.…”
Section: Fundingmentioning
confidence: 99%
“…There is a need to review each particular case in detail to define these features. In recent years, there has been an improvement in selecting patients susceptible to surgery and other treatment therapies by sleep surgeons [7]. The use of drug-induced sleep endoscopy (DISE) [8,9] has allowed a more precise understanding of airway collapse including different shapes and degrees of severity.…”
Section: Introductionmentioning
confidence: 99%
“…Verse et al [26] recommended that, isolated hyoid suspension can be used as a surgical treatment of OSA in patients with suspected hypoglossal obstruction.…”
Section: Disucssionmentioning
confidence: 99%
“…The Wisconsin Sleep Cohort Study, established over two decades ago, demonstrated a relationship between OSA and obesity, thus, as obesity increases globally, the incidence of OSA is expected to increase as well [3]. The standard treatment for OSA is continuous positive airway pressure (CPAP), which is effective but fraught with challenges of maintaining adherence [4]. Other treatment options include mandibular advancement devices (MAD), weight loss, behavior modifications, and surgical options [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for OSA is continuous positive airway pressure (CPAP), which is effective but fraught with challenges of maintaining adherence [4]. Other treatment options include mandibular advancement devices (MAD), weight loss, behavior modifications, and surgical options [4,5].…”
Section: Introductionmentioning
confidence: 99%